Visible/near-infrared luminescence and concentration effects of Pr3+-doped Sr2Al2GeO7 downconversion phosphors - Tiantian Shen; Shanshan Zhao; An Su; Haisheng Liu; Fayi Chen; Benchun Li; Xinxin Han; Dechao Yu; Dawei Zhang (APL Materials, 2024)
The Pr3+ ion has been widely doped into various materials as a red and near-infrared (NIR) emitting center for applications in lighting and solar spectrum downconversion. Herein, the preparation of a new library of Pr3+-doped Sr2Al2GeO7 phosphors was proved by powder x-ray diffraction patterns and Rietveld refinements and characterized by a scanning electron microscope with energy-dispersive x-ray spectrometry. The Sr2Al2GeO7:Pr3+ sample strongly absorbs blue photons over 420–500 nm and yields intense visible emissions with dominant peaks around 490 nm from the Pr3+ 3P0 → 3H4 transition, as well as robust NIR emission bands over 800–1200 nm. In addition to the typical transitions of 1D2 → 3F2 at 880 nm, 1G4 → 3H4 at 1000 nm, and 1D2 → 3F3,4 at 1070 nm, the distinguishable NIR emission at 929 nm was demonstrated from the 3P0 → 1G4 transition via static and dynamic spectroscopic analysis. Most interestingly, for the 3P0 blue-excited state, a considerably elevated concentration of about 10%Pr3+ was optimal for the visible/NIR emissions, in stark contrast to the diluted optimal 1%Pr3+ for the 1D2 state. The relevant cross-relaxation from the 3P0 and 1D2 states between Pr3+ was comprehensively treated by theoretical speculations and experimental results. Such concentrated Pr3+ blue activators would significantly facilitate the blue-to-NIR downconversion through a desired two-step sequential transition from the 3P0 initial state to the 1G4 intermediate level for quantum efficiency exceeding unity. The current results would consolidate the basis of concentrated Pr3+ donors to promote the novel Pr3+/Yb3+ codoping downconversion for greatly increasing Si solar cell efficiency.